Gender Related Access Complications After TEVAR: Analysis from the Retrospective Multicentre Cohort GORE® GREAT Registry Study. (August 2020) - Lomazzi, Chiara; Mascoli, Chiara; de Beaufort, Hector W.L.; Cao, Piergiorgio; Weaver, Fred; Milner, Ross; Fillinger, Mark; Verhoeven, Eric; Grassi, Viviana; Gargiulo, Mauro; Trimarchi, Santi; Piffaretti, Gabriele; et al.
Abstract : Objective: The Global Registry for Endovascular Aortic Treatment (GREAT), a retrospective sponsored registry, was queried to determine the incidence and identify potential predictors of access related complications after TEVAR. Methods: This is a multicentre, observational cohort study. For the current study, all patients were treated only with the Conformable GORE® TAG® Thoracic Endoprosthesis and GORE® TAG® Thoracic Endoprosthesis devices for any kind of thoracic aortic disease. All serious adverse events within 30 days of the procedure were documented by sites. The following were considered access related complications: surgical site infection, pseudoaneurysm, avulsion, dissection, arterial bleeding, access vessel thrombosis/occlusion, seroma, and lymphocoele. Results: A total of 887 patients was analysed: most of the cases had an operative indication for TEVAR of degenerative atherosclerotic aneurysm ( n = 414, 46.7%) and type B dissection ( n = 270, 30.4% either complicated or uncomplicated). Two hundred and ninety-five patients (33.3%) were female. The overall access related complication rate was 2.8% ( n = 25): 4.7% ( n = 14) in women and 1.8% ( n = 11) in men ( p = .013). After adjustment for age, urgency, device diameter, introducer sheath (≥24Fr vs. ≤ 24Fr), access vessel diameters, and access method, female gender was significantly associated with the risk of access complications (OR 2.85; p = .038). Brachial artery for access was also found to be an independent predictor of access related complications (OR 8.32; p < .001). Conclusion: This analysis suggests that women may have a higher access related complication rate after TEVAR, irrespective of the clinical setting, type of aortic disease, and device sizing.